PENGARUH SERTIFIKASI GURU TERHADAP PENINGKATAN KINERJA GURU PAI DI SMP DAN MTs - Nurhattati Fuad (Jurnal Manajemen Pendidikan, 2017)
This study aim to evaluate the effect of teacher certification on improving the performance of PAI teachers in SMP and MTs in 23 regencies / cities spread across 14 provinces. This research was conducted for 3 (three) months. This research is evaluative research. The results show that: (1) Certification for Teachers of PAI and Arabic in MTs and PAI teachers in junior high schools has been run in accordance with existing guidelines. (2) the performance of Teachers of PAI clusters and the language of direction in MTs and PAI teachers in certified junior high schools is close to compliance with the standards, but there are still teacher weaknesses in the use of IT in learning and seeking enrichment materials from the virtual world. (3) Teacher certification affect teacher performance. (4) There are several factors that affect teacher performance, both from internal and external aspects.